Inula helenium loaded nanofibers mat for medical application - CESUR, SÜMEYYE; AYAZ SEYHAN, SERAP; BİLĞİÇ ALKAYA, DİLEK; GÜNDÜZ, OĞUZHAN (My University, 2023)
Cancer is one of the leading causes of death worldwide. Biomaterials produced with nanotechnological methods for cancer treatment are more effective and complementary than existing treatment strategies. Nanofiber scaffolds are biomaterials that can be used in cancer treatment and can be produced in composites with biocompatible polymers and anti-cancer drugs, plant extracts. The electrospin device used for the production of these materials creates nanofiber networks by providing the electric field between the needle tip and the metal collector, which transmits the polymer solution. PLA is a biodegradable synthetic material preferred in tissue engineering studies and is a biocompatible, high mechanical strength, low cost polymer suitable for use in drug delivery systems. PVP is a polymer with good adhesion, high physiological compatibility, low toxicity and easily soluble in most organic solvents, especially used in the pharmaceutical industry. The extract of the plant Inula helenium, whose main component consists of sesquiterpene lactones, is also used in treatments for cancer. This component, which has various biological activities, has a significant anti-cancer effect. In this study, the polymer ratio used in the production of nanofiber scaffold obtained by adding Inula helenium extract is 75% PLA-chloroform / 25% PVP-ethanol and 1% Tween 80. The surface morphology of the produced fiber material was determined according to the results in the SEM images. The diameters of the fibers were measured and given in the histogram graph. FT-IR for chemical structure between bonds and DSC tests for thermal behavior analysis were applied. Tensile test was performed for mechanical analysis. Swelling-degradation test was performed and drug release kinetic data were calculated by UV spectrophotometer. In addition, its effectiveness on cancerous cells was examined by MTT analysis. In conclusion, Inula helenium extract-loaded nanofibers can reduce the risk of local recurrence of cancer after surgery and can be directly implanted into solid tumor cells for treatment
Keywords: I. helenium; Electrospin; Biomaterials; Cancer treatment